Onycholysis due to trauma - Patricia Chang; Monica Vanesa Vásquez Acajabón (Our Dermatology Online, 2014)
Female patient, 35 years old who came to the private office due to discoloration of her left thumbnail and little pain since 1 month ago. Clinical examination shows nail disease on her left thumbnail with onycholysis and dyschromia, dermatoscopy showed white-yellowish discoloration (Fig. 1A, B). The rest of the clinical examination was normal. Patient use to using acrylic nails since 2 years ago and denied some trauma at the nail. The diagnosis of onycholysis due to trauma was done and recommended her not to use acrylic nail, maintain the nail short and avoid wetness.